Modified Born series with virtual absorbing boundary enabling large-scale electromagnetic simulation - Pinxuan He; Jiamin Liu; Honggang Gu; Hao Jiang; Shiyuan Liu (Communications Physics)
Abstract Numerical electromagnetic field solvers are significant for nanophotonic and photoelectronic technology, especially for computational imaging, metasurface, and biomedical microscopy, in which large-scale simulations serve as the core. Conventionally, these simulations use absorbing boundary conditions (ABC) to simulate open-domain systems. However, the existing ABCs require large memory to sufficiently suppress reflection at boundaries, which is prohibitive for large-scale applications. This work proposes a virtual absorbing boundary condition based on the angular spectrum method (ASM) to reduce the memory usage of ABC. The ASM is used to cover the polluted field in the boundary region, which eliminates the need to store the field in the boundary region. Combined with the Fourier transforms-based modified Born series, memory usage can be reduced to a level close to the theoretical limit. This proposed method offers a substantial boost for applications related to large-scale simulations and memory-constrained devices like GPU.